Essential university physics / Richard Wolfson - Wolfson, Richard
"Based on Physics for Scientists and Engineers by Wolfson and Pasachoff, Essential University Physics retains many of the lauded features of the original text, while introducing new pedagogical elements derived from physics education research. The text focuses on the fundamentals of physics, teaches sound problem-solving skills, emphasizes conceptual understanding, and makes connections to the real world. Features such as annotated figures and step-by-step problem-solving strategies help provide a clear learning path for students."